Effects of Learner Variables on Chinese Bilingual Undergraduates' Intercultural Sensitivity and Effectiveness - Meihua Liu (MDPI AG, 2022)
This study investigated the effects of learner variables on Chinese bilingual undergraduates' intercultural sensitivity and effectiveness. A total of 439 students from different universities answered a battery of questionnaires. Major findings were: (a) the participants reported a moderate to high level of intercultural sensitivity and a moderate level of intercultural effectiveness; (b) no significant gender difference occurred in intercultural sensitivity and effectiveness, except for Interaction Engagement and Respect for Cultural Differences; (c) intercultural sensitivity and effectiveness were significantly positively related to and predicted each other; (d) confidence in learning English, self-efficacy in learning English and English classroom anxiety significantly predicted students' intercultural sensitivity; and (e) English classroom anxiety, English learning motivation, and self-efficacy in learning English significantly predicted students' intercultural effectiveness. Based on these findings, a path model was constructed which explains the relations among affect, intercultural communication sensitivity, effectiveness and competence.